Research on the Educational Practice and Path of College Students’ Border-area Study Tour from the Perspective of Disciplinary Integration——A Case Study of "Starlight Exploration Journey: Xingkai Lake Study Tour" - Tianyi Deng; Jingyuan Peng; Tianhe Kang; Wennan Li (Education Research on Study Tours and Practice, 2026)
Border-area study tour serves as a crucial practical carrier for implementing the fundamental task of fostering virtue through education, cultivating college students’ feelings of family and country, and deepening their awareness of national security and ecological protection. Currently, study tours for college students often face issues such as thematic vagueness, unclear alignment with academic stages, and weak connections with local resources. Based on the concepts of interdisciplinary integration and experiential learning, and targeting the 18-25-year-old college student group, this paper systematically constructs a two-day-one-night themed study route, "Starlight Exploration Journey", leveraging the unique resources of the Xingkai Lake area, including its boundary lake wetland, historical and cultural sites, rare species protection base, and national security education resources. Positioning the course as a "Walking National Gateway Classroom", it integrates local resources around four dimensions: "Ecological Border", "Historical Border", "Developmental Border", and "Security Border". The course designs a series of inquiry-based activities covering wetland ecological investigation, prehistoric civilization tracing, sika deer protection practice, AR safety training, and lakeside geological cognition. Through the implementation path of "pre-trip guidance – on-site immersion – summary and sublimation" and a diversified evaluation system, it guides students to achieve deep integration of knowledge acquisition, ability enhancement, and value shaping. This effectively inspires their awe, commitment to protect, and love for the natural and cultural heritage of the motherland’s border areas, providing a replicable practical paradigm for colleges and universities to conduct high-quality, characteristic border national conditions education.